Consensus on the treatment of alopecia areata - Brazilian Society of Dermatology, - Paulo Müller Ramos; Alessandra Anzai; Bruna Duque-Estrada; Daniel Fernandes Melo; Flavia Sternberg; Leopoldo Duailibe Nogueira Santos; Lorena Dourado Alves; Fabiane Mulinari-Brenner (Sociedade Brasileira de Dermatologia, 2021)
Abstract Background: Alopecia areata is a highly frequent disease with an impact on quality of life and several treatment options with little clinical confirmatory evidence. Objective: To disseminate the recommendations of Brazilian dermatologists with expertise in the treatment of alopecia areata. Methods: Eight specialists with expertise in alopecia areata from different university centers were appointed by the Brazilian Society of Dermatology to reach a consensus on its treatment. Based on the adapted DELPHI methodology, the relevant elements were considered; then, an analysis of recent literature was carried out and the consensus was written down. Consensus on the management of alopecia areata was defined with the approval of at least 70% of the panel. Results/Conclusions: Intralesional injectable corticotherapy was considered the first option for localized disease in adults. In extensive cases with signs of activity, systemic corticosteroid therapy should be considered and can be used together with immunosuppressants (corticosteroid-sparing agents). The use of an immunosensitizer (diphencyprone) is an option for stable long-term cases. Evaluation of side effects is as important as the rate of hair regrowth.